2020
DOI: 10.1115/1.4046387
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Wellbore Stability With a Modified Lade Failure Criterion

Abstract: The importance of evaluating wellbore stability in analyzing and estimating the efficiency of drilling directionally into oil and gas reservoirs is well known. Geomechanical data and failure criterion can be used to model and control rock mass behavior in response to the stresses imposed upon it. Understanding and managing the risks of rock mass deformation significantly improve operational processes such as wellbore stability, sand production, and hydraulic fracturing. The modified Lade failure criterion is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Breaking down water-in-oil emulsions in crude oil can be difficult, requiring complex treatments for large scale processing plants. A broad range of novel technologies and their applications, introduced in recent years, plays a substantial role in improving standards of living and access to energy and resources, such as CO2 emission [8] , energy resources [9] , enhanced oil recovery [10] , iron corrosion [11] , bioresources [12] , [13] , [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Breaking down water-in-oil emulsions in crude oil can be difficult, requiring complex treatments for large scale processing plants. A broad range of novel technologies and their applications, introduced in recent years, plays a substantial role in improving standards of living and access to energy and resources, such as CO2 emission [8] , energy resources [9] , enhanced oil recovery [10] , iron corrosion [11] , bioresources [12] , [13] , [14] .…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Kamgue Lenwoue et al believed that the elastic model and the Mohr-Coulomb criterion were not accurate enough to evaluate the well wall stability, so the Mogi-Coulomb criterion was used to analyze the well wall stability [8]. In 2020, Bahrami et al based on previous research proposed that the improved Lade failure criterion be used as the most accurate failure criterion and found that, compared with the application of other failure criteria, the application of the improved Lade failure criterion could accurately predict the wellbore instability without the input of reservoir structure boundary knowledge or core test data [9].…”
Section: Related Workmentioning
confidence: 99%
“…The small size of the aphron's bubbles provide them with high inter-facial areas that makes them amenable to being pumped, in a similar way to water, without risk of collapse [3]. A broad range of novel technologies and their applications, introduced in recent years, play a substantial role in improving standards of living and access to energy and resources, such as oil pretreatment [4,5], biofuels [6][7][8][9], corrosion [10,11], carbon dioxide [12][13][14], wastewater treatments [15,16], flow in porous media [17][18][19], bioresource technology [6][7][8]13,15,[20][21][22][23][24], Enhanced Oil Recovery [25][26][27][28][29][30]. CGA-based fluid technologies are being deployed with success in horizontal and high-angle wellbore trajectories in highly pressuredepleted reservoirs [31].…”
Section: Introductionmentioning
confidence: 99%